Exercise-Induced Changes of Multimodal Interactions Within the Autonomic Nervous Network - Vieluf, Solveig; Hasija, Tanuj; Jakobsmeyer, Rasmus; Schreier, Peter J.; Reinsberger, Claus (Frontiers in Physiology, 2019)
Physical exercise has been shown to modulate activity within the autonomic nervous system (ANS). Considering physical exercise as a holistic stimulus on the nervous system and specifically the ANS, uni- and multimodal analysis tools were applied to characterize centrally driven interactions and control of ANS functions. 19 young and physically active participants performed treadmill tests at individually determined moderate and high intensities. Continuous electrodermal activity (EDA), heart rate (HR), and skin temperature at wrist (Temp) were recorded by wireless multisensor devices (Empatica® E4, Milan, Italy) before and 30 min after exercise. Artifact-free continuous 3 min intervals were analyzed. For unimodal analysis, mean values were calculated, for bimodal and multimodal analysis canonical correlation analysis (CCA) was performed. Unimodal results indicate that physical exercise affects ANS activity. More specifically, Temp increased due to physical activity (moderate intensity: from 34.15°C to 35.34°C and high: from 34.11°C to 35.09°C). HR increased more for the high (from 60.76bpm to 79.89bpm) than for the moderate (from 64.81bpm to 70.83bpm) intensity. EDA was higher for the high (pre: 8.06 S and post: 9.37μS) than for the moderate (pre: 4.31μS and post: 3.91μS) intensity. Bimodal analyses revealed high variations in correlations before exercise. The overall correlation coefficient showed varying correlations in pretest measures for all modality pairs (EDA-HR, HR-Temp, Temp-EDA at moderate: 0.831, 0.998, 0,921 and high: 0.706, 0, 0.578). After exercising at moderate intensity coefficients changed little (0.828, 0.744, 0.994), but increased substantially for all modality pairs after exercising at high intensity (0.976, 0.898, 0.926). Multimodal analysis confirmed bimodal results. Exercise-induced changes in ANS activity can be found in multiple ANS modalities as well as in their interactions. Those changes are intensity-specific: with higher intensity the interactions increase. Canoncial correlations between different ANS modalities may therefore offer a feasible approach to determine exercise induced modulations of ANS activity